If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(t + -1) = 9(r + -4) Reorder the terms: 6(-1 + t) = 9(r + -4) (-1 * 6 + t * 6) = 9(r + -4) (-6 + 6t) = 9(r + -4) Reorder the terms: -6 + 6t = 9(-4 + r) -6 + 6t = (-4 * 9 + r * 9) -6 + 6t = (-36 + 9r) Solving -6 + 6t = -36 + 9r Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 6t = -36 + 6 + 9r Combine like terms: -6 + 6 = 0 0 + 6t = -36 + 6 + 9r 6t = -36 + 6 + 9r Combine like terms: -36 + 6 = -30 6t = -30 + 9r Divide each side by '6'. t = -5 + 1.5r Simplifying t = -5 + 1.5r
| 1.6(d+-2)=40 | | y^2-3x-6y=8 | | 15y^2+29y+12= | | 49-54= | | 9x+2(x-1)=11x+8 | | 3(2x-1)+x=-x-3 | | 8k+k-7-10k= | | 3(2x+4)+6=2(x-5) | | 42m=999 | | 4-3x=26 | | 3x^2+17x+8= | | 42m=9999 | | 1000000+100000000000000000000000000000= | | 3(2x+4)+6=2x-5 | | 180=16r^2 | | 15=-9+x | | 9r^3-36r=0 | | =350-14x | | 20=-5y-3x | | -154x=6-3x | | Y-4y=-60 | | -x=5x-12 | | -24x+9=-3x-4 | | 5x-7x-3=8 | | f(x)=4xsquared-13x+3 | | 3.5-.60+8.3-4.2=t | | 4(m+6)=24+4m | | 2x-11=2x | | 2(-7.5)= | | Q^2=-9 | | 13t^2+5t-8=0 | | 7-3x=2y-9.6x |